Gastric Necrosis and Perforation Following Massive Gastric Dilatation in an Adolescent Girl: A Rare Cause of Acute Abdomen - Zvizdic, Zlatan; Jonuzi, Asmir; Djuran, Aleksandra; Vranic, Semir (Frontiers in Surgery, 2019)
Gastric necrosis with perforation is a rare and potentially life-threatening condition in childhood beyond the neonatal period. We report a case of gastric necrosis and perforation of a portion of the great curvature due to a massive gastric dilatation caused by pathological aerophagia in a 13-year-old, mentally impaired adolescent girl. Despite the successful surgical treatment, the patient’s condition rapidly deteriorated postoperatively and she died due to the multisystem organ failure and multiple infections. In addition, we surveyed the literature on this rare condition and assessed the preventive actions to reduce this life-treating condition.